Depresija kot spremljevalka telesnih bolezni - Rifel, Janez (Farmacevtski vestnik, 2023)
Depression is a frequent companion of physical ill- nesses, especially when these significantly affect patient's daily life. We have to pay attention to the co-occurrence of depression in patients with dia- betes, cardiovascular diseases, neurological and neurodegenerative diseases, cancer patients, and patients with chronic pain. In the most at-risk groups of patients, screening for the presence of depression using questionnaires might be recommended. In the treatment of depression with the simultaneous presence of physical illness and the use of various drugs, it is necessary to take into account the pres- ence of concomitant diseases and conditions and possible interactions between drugs. The treatment of a multimorbid patient must be in-depth, patient- oriented and often requires the inclusion of several healthcare team members
Keywords: depresija; depression; interaction; interakcija; multimorbidity; multimorbidnost